Selenium fractionation from plasma, muscle and liver of Nile tilapia (Oreochromis niloticus) - Silva, Fábio A. [UNESP]; Cavecci, Bruna [UNESP]; Baldassini, Welder A. [UNESP]; Lima, Paula M. [UNESP]; Moraes, Paula M. [UNESP]; Roldan, Paulo S.; Padilha, Cilene C.F. [UNESP]; Padilha, Pedro M. [UNESP] (Springer Nature, 2013)
This paper presents the results obtained from selenium fractionation in plasma, muscle and liver samples of Nile tilapia's (Oreochromis niloticus) after protein separation. The plasma, muscle and liver proteome was obtained by 2D-PAGE, and selenium in protein spots was qualitatively and quantitatively determined by synchrotron radiation X-ray fluorescence and graphite furnace atomic absorption spectrometry (GFAAS). The fluorescence spectra indicated the presence of selenium in three protein spots of plasma, two of muscle and one of liver. Selenium was found to be distributed mainly in proteins with a molar mass smaller than 57.0 kDa and with pI in the range of 5.9-9.6, with one exception in the plasma sample, which presented protein with a molar mass of 60.0 kDa. After acid mineralization of the protein spots, a GFAAS determination of the concentration of selenium bound to these proteins indicated a range of 1.35-6.82 mg per g of protein. © 2013 Springer Science+Business Media New York.
Keywords: 2D-PAGE; GFAAS; Metalloproteins; Selenium; SR XRF